Is transnasal TEE imaging a viable alternative to conventional TEE during structural cardiac interventions to avoid general anaesthesia? A pilot comparison study of image quality. Issue 1 (March 2017) - Klettas, Dimitris; Alcock, Emma; Dworakowski, Rafal; MacCarthy, Philip; Monaghan, Mark
Abstract : Aim: The role of transoesophageal echocardiography in cardiac interventional structural procedures is well established and appreciated. However, the need for general anaesthesia (GA) throughout the procedure remains a controversial issue. The aim of the present study is to assess the feasibility and imaging quality of using a transnasal microrobe that allows the usage of conscious sedation in patients who undergo cardiac structural interventional procedures without missing the benefits, guidance and navigation of conventional trans-procedural TEE. Methods: We analysed the trans-procedural images of 24 consecutive patients who underwent TAVI, TMVI or ASD/PFO closure, using a transnasal 2D microprobe (PHILIPS) and then we compared them with images taken by using a conventional 3D TEE probe (PHILIPS). In particular, we compared the imaging quality of the two probes regarding: (1) The anatomy, visualisation of valvular calcification and transvalvular colour Doppler of the aortic and mitral valve; (2) the imaging quality of PFO, ASD and interatrial communication colour flow; (3) the imaging of left ventricle systolic function and pericardial space and (4) transgastric imaging. Results: All images were graded with a scale from 5 to 1. The average grade of imaging quality in the mitral valve was: anatomy, 4.3; calcification, 3.8; colour Doppler, 4.2. The average grade of imaging quality in the aortic valve was: anatomy, 4.3; calcification, 3.7; colour Doppler, 4.3. The average grade of imaging quality in PFO/ASD was 4.3. The average grade of imaging quality in LV/pericardial space was 4.2. The average grade of imaging quality in transgastric imaging was 4.1. Conclusion: These results suggest that transnasal TEE can provide good anatomical image quality of relevant cardiac structures during cardiac structural interventions and this may facilitate these procedures being performed during conscious sedation without having to lose TEE guidance.